Ellipsometry studies on anodic aluminium oxide (AAO)growth mechanism on high purity aluminium plate - Lim, Leng Khoon (2014)
Aluminum anodizing was conventionally used as surface protective coating or decorative purposes in the past. With the emerge of nanotechnology in recent years, new method of aluminum anodizing which is known as anodic aluminum oxide (AAO) generates new application such as filtration membranes or nanomaterial templates. Due to this novelty in the field of material science, many attentions had been directed towards the use and research of AAO. In the biomedical field, AAO was used many applications such as pathogens microfiltration, biomolecules quantification, drug delivery etc, However, it had been a challenge to produce the necessary microstructure for all the mentioned applications. This report presents the relationship between the anodizing parameters such as voltage, temperature and time and results such as film thickness and pores by using high purity aluminum plate. Such study would useful to control the required specification of the microstructure. Thickness increases together with voltage, time and temperature where these parameters are the contributing factors to the rate of anodizing. Many characterization methods are available but most of them are destructive to measure film thickness. As such ellipsometry is non-destructive technique which is chosen in this project.